The Role of Cognitive Computing and Collective Cognitive Computing in the Future Internet - Williams, Andy; Petrovic, Nenad (My University, 2020)
INTRODUCTION: The European Union, the United States, and China have all had, or currently have, programs to support research into the development of their vision of the Internet of the future. OBJECTIVES: To explore whether and if so how cognitive computing or collective cognitive computing is likely to be a critical aspect of all of these visions of the future Internet, even where these visions differ wildly. METHODS: An analysis is performed to assess whether and how AGI and GCI might be used to optimize achievement of the EU’s vision for a future Internet. And an analysis is performed to determine whether and if so how AGI and GCI might be used to optimize achievement of China’s potentially very different vision for a future Internet. RESULTS: AGI and GCI appear to create the possibility of future Internet technology that self-assembles in different ways according to the users, so that it simultaneously might maximize outcomes in implementing potentially conflicting visions of that future Internet. CONCLUSION: The conceptual example of customizing a news media website for two individual users of opposite political persuasions suggests that while the overhead of customizing such services might potentially result in massively increased storage and processing overhead, within a network of cooperating services in which this customization reliably creates value, this is potentially a significant opportunity.
Keywords: Artificial General Intelligence; General Collective Intelligence; Human-Centric Functional Modeling; Internet